Ultrahigh-strength three-dimensional network graphene / amorphous carbon composite material and preparation method thereof
The two-step strategy is used to prepare ultra-high strength three-dimensional mesh graphene/amorphous carbon composite materials using acrylamide and water-soluble sugar hydrogels, which solves the problems of complex preparation process, long periods, high costs and poor mechanical properties of traditional graphite bulk carbon materials, and achieves high strength and excellent mechanical properties of material preparation.
Patent Information
- Application Number
- CN202510014947.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The existing graphite bulk carbon materials have complex preparation processes, long cycles, high raw material costs and poor mechanical properties, making it difficult to effectively improve material strength.
Using a two-step strategy, acrylamide and water-soluble sugar hydrogels were used as starting materials, and ultra-high strength three-dimensional mesh graphene/amorphous carbon composites were prepared through pretreatment and sintering.
The high strength and excellent mechanical properties of the material are achieved, the compressive strength can be as high as 303MPa and the flexural strength can be as high as 203MPa, which is significantly better than traditional graphite-based materials, simplifying the process flow and reducing production costs.
Smart Images

Figure CN119797920A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon materials, and in particular relates to an ultra-high-strength three-dimensional mesh graphene / amorphous carbon composite material and a preparation method thereof. Background Art
[0002] Graphite materials have been widely used in many fields due to their excellent properties, including high strength, high conductivity, high temperature resistance and corrosion resistance, especially in high-end technical fields such as aerospace, electronics, metallurgy and nuclear industry, becoming an important basic material. In addition, graphite materials are also widely used in battery electrodes, thermal conductive materials, high temperature resistant components and catalyst carriers. With the advancement of science and technology, the demand for graphite materials continues to grow, but there are many problems in the existing graphite material preparation process, which limits its further application.
[0003] At present, the preparation cycle of traditional high-strength graphite block carbon materials is long, the raw material cost is high, and the material strength is low. Its preparation usually relies on coke and binder as starting materials, and undergoes a complex and lengthy carbonization and graphitization process, resulting in a long production cycle, and the ability to control the microstructure during the preparation process is limited, which limits the strength improvement of the final material. Therefore, optimizing the structural design of graphite-based carbon materials and improving their performance remain the main challenges currently faced.
[0004] In order to improve the mechanical properties of graphite materials, traditional methods mainly improve the microstructure by purifying raw materials and introducing reinforcing agents. For example, petroleum coke is purified by chemical methods, or reinforcing agents such as sulfonated graphene are introduced to improve mechanical properties. In addition, some studies have successfully controlled the graphite material from sp 2 to sp 3 The hybrid transformation further improves the bending and compressive strength of the material. However, these traditional processes still have bottlenecks in the design and control of microstructures, especially in how to effectively improve the strength of materials.
[0005] In recent years, the synthesis technology of carbon-based materials has made some progress, including the synthesis methods using fibers, aerogels and composite materials. However, these methods are prone to cause cracks and pores due to the significant shrinkage and stress of the materials during the carbonization process, making it difficult to achieve the preparation of bulk materials at a macroscopic scale. Therefore, developing new preparation methods to solve these problems has become an important research direction in the current field of carbon materials. Summary of the invention
[0006] In order to solve the problems of complexity, long cycle, high cost of raw materials, poor mechanical properties, etc. in the preparation process of existing graphite block carbon materials. The present invention proposes an ultra-high strength three-dimensional mesh graphene / amorphous carbon composite material and a preparation method thereof, that is, a new two-step strategy is adopted to synthesize a high-strength graphite / amorphous carbon composite material by using polyacrylamide and water-soluble sugar hydrogel as starting materials. The composite material exhibits excellent mechanical properties, with a compressive strength of up to 303MPa and a flexural strength of up to 203MPa, which is significantly better than traditional graphite-based materials.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] One of the technical solutions of the present invention:
[0009] A method for preparing an ultra-high-strength three-dimensional mesh graphene / amorphous carbon composite material comprises the following steps:
[0010] A two-step method is adopted to sequentially pretreat and sinter a hydrogel prepared from acrylamide, water-soluble sugars, and N,N'-methylenebisacrylamide, and finally prepare the ultra-high-strength three-dimensional network graphene / amorphous carbon composite material;
[0011] Wherein, the sintering process adopts spark plasma sintering or hot pressing sintering.
[0012] Preferably, the preparation process of the hydrogel is:
[0013] The acrylamide, water-soluble sugar and N,N'-methylenebisacrylamide are mixed and dissolved in deionized water, and stirred to form a uniform solution; and then dried at 50-200° C. to obtain a hydrogel.
[0014] Preferably, in terms of weight percentage, the acrylamide, water-soluble sugar and N,N'-methylenebisacrylamide are 1-30%, 5-60% and 0.05-3% respectively, and the balance is deionized water.
[0015] Preferably, in terms of weight percentage, the acrylamide, water-soluble sugars and N,N'-methylenebisacrylamide are 7.39%, 24.65% and 0.18% respectively.
[0016] Preferably, the water-soluble sugars include one or more of glucose, fructose, galactose, maltose, sucrose, lactose or oligofructose.
[0017] Preferably, the pretreatment process is:
[0018] The hydrogel is heat-treated in a muffle furnace to obtain a pre-treated product A;
[0019] The pre-treated product A is heated to 400°C-1400°C at a heating rate of 1-20°C / min in an inert environment, and then kept at this temperature for 1 hour to obtain a pre-treated product B;
[0020] The pretreated product B is crushed and ball-milled in a ball mill to obtain pretreated powder.
[0021] Preferably, the conditions of the heat treatment process are:
[0022] The temperature is raised to 140-350°C at a heating rate of 0.1-20°C / min, and maintained for 0.5-30h after reaching the target temperature.
[0023] Preferably, the conditions of the heat treatment process are: heating to 220°C at a heating rate of 0.5°C / min, and keeping the temperature for 2 hours after reaching the target temperature.
[0024] Preferably, the inert environment is vacuum or argon or nitrogen.
[0025] Preferably, the ball milling treatment conditions are: ball-to-material ratio 1-20:1, ball milling speed 100-600 r / min, and ball milling time 6-48 h.
[0026] Preferably, the ball milling treatment conditions are: ball-to-material ratio 3:1, ball milling speed 200 r / min, and ball milling time 16 h.
[0027] Preferably, the parameters of the sintering process are: heating rate 5-300°C / min, sintering temperature 1600-2800°C, applied pressure 10-200MPa, and holding time 1-120min.
[0028] Preferably, the parameters of the sintering process are: heating rate 150°C / min, sintering temperature 2400°C, applied pressure 60MPa, and holding time 10min.
[0029] The second technical solution of the present invention:
[0030] The above preparation method prepares an ultra-high-strength three-dimensional mesh graphene / amorphous carbon composite material.
[0031] Compared with the prior art, the present invention has the following advantages and technical effects:
[0032] The present invention discloses an ultra-high strength three-dimensional mesh graphene / amorphous carbon composite material and a preparation method thereof. A two-step strategy is adopted to synthesize a high-strength graphite / amorphous carbon composite material by using acrylamide and glucose hydrogel as starting materials. Experiments show that acrylamide preferentially undergoes graphitization reaction to form an internal network structure, and a three-dimensional mesh graphene / amorphous carbon composite material can be constructed by utilizing the different graphitization tendencies of acrylamide and glucose. This new composite material exhibits excellent mechanical properties, with a compressive strength of up to 303MPa and a flexural strength of up to 203MPa, which is significantly better than traditional graphite-based materials. This method provides a new approach for the development of high-strength graphite-based carbon materials.
[0033] The two-step strategy of the present invention not only solves the bottleneck of traditional methods in microstructure design, but also significantly shortens the preparation cycle and reduces production costs. It successfully prepares graphite-based carbon materials with high strength and excellent mechanical properties, laying the foundation for the further development of graphite materials in industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0035] Figure 1 This is a bending strength curve of the three-dimensional network graphene / amorphous carbon composite material prepared in Example 1;
[0036] Figure 2 This is a compression strength curve of the three-dimensional network graphene / amorphous carbon composite material prepared in Example 1;
[0037] in Figure 1 and Figure 2 1#, 2#, and 3# are three tests of the same sample of the three-dimensional network graphene / amorphous carbon composite material prepared in Example 1;
[0038] Figure 3 This is a microstructure diagram of the three-dimensional network graphene / amorphous carbon composite material prepared in Example 1;
[0039] Figure 4 This is a wear rate diagram of the three-dimensional network graphene / amorphous carbon composite material prepared in Example 1. DETAILED DESCRIPTION
[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0041] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0045] The present invention selects acrylamide and water-soluble sugar substances as starting materials and adopts a two-step method to prepare a high-strength graphite / amorphous carbon composite material. The specific method for preparing a three-dimensional network graphene / amorphous carbon composite material comprises the following steps:
[0046] (1) weighing the raw materials for use: according to the weight percentage, acrylamide: water-soluble sugar: N, N'-methylenebisacrylamide = (1-30%): (5-60%): (0.05-3%), the balance is deionized water;
[0047] (2) Pretreatment process:
[0048] 21) mixing acrylamide, water-soluble sugar and N,N'-methylenebisacrylamide and dissolving them in deionized water, stirring to form a uniform solution; gelling the solution at 50-200° C. and drying to obtain a hydrogel; and then heat-treating the hydrogel in a muffle furnace to obtain a pre-treated product A;
[0049] 22) heat-treating the pretreated product A under inert conditions at 400° C.-1400° C. for 1 hour to obtain a pretreated product B;
[0050] 23) crushing the pretreated product B, and ball milling it in a ball mill to obtain a pretreated powder;
[0051] (3) The pretreated powder is loaded into a C / C composite material mold with a diameter of 10-100 mm and sintered using spark plasma sintering (SPS) technology or hot pressing sintering.
[0052] In some preferred embodiments, the water-soluble sugars include one or more of glucose, fructose, galactose, maltose, sucrose, lactose or oligofructose.
[0053] In some preferred embodiments, based on weight percentage, acrylamide: water-soluble sugar: N,N'-methylenebisacrylamide = 7.39%: 24.65%: 0.18%.
[0054] In some preferred embodiments, the temperature during the drying process in step (2) is 60°C.
[0055] In some preferred embodiments, the conditions of the heat treatment process in step 21) are:
[0056] The temperature is raised to 140-350°C at a heating rate of 0.1-20°C / min, and maintained for 0.5-30h after reaching the target temperature.
[0057] In some preferred embodiments, the conditions of the heat treatment process in step 21) are: heating to 220°C at a heating rate of 0.5°C / min, and keeping the temperature for 2 hours after reaching the target temperature.
[0058] In some preferred embodiments, the inert environment in step 22) is vacuum or argon or nitrogen.
[0059] In some preferred embodiments, the ball milling conditions in step 23) are: ball-to-material ratio 1-20:1, ball milling speed 100-600 r / min, and ball milling time 6-48 h.
[0060] In some preferred embodiments, the ball milling conditions in step 23) are: ball-to-material ratio 3:1, ball milling speed 200 r / min, and ball milling time 16 h.
[0061] In some preferred embodiments, the parameters of the sintering process are: heating rate 5-300° C. / min, sintering temperature 1600-2800° C., applied pressure 10-200 MPa, and holding time 1-120 min.
[0062] In some preferred embodiments, the parameters of the sintering process are: heating rate 150°C / min, sintering temperature 2400°C, applied pressure 60MPa, and holding time 10min.
[0063] Through this process, a high-density bulk carbon material is finally prepared, which not only has excellent mechanical properties, but also overcomes the complexity and long cycle problems in the traditional graphite bulk material preparation process, and achieves high strength and high wear resistance of the material.
[0064] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0065] The "parts" described in the present invention, unless otherwise specified, refer to parts by mass.
[0066] The raw materials used in the present invention are all purchased from the market.
[0067] The technical solution of the present invention is further illustrated by the following embodiments.
[0068] Example 1
[0069] A method for preparing a three-dimensional network graphene / amorphous carbon composite material comprises the following steps:
[0070] The first step is the pretreatment step. 200 grams of glucose, 60 grams of acrylamide and 1.5 grams of N, N'-methylenebisacrylamide are mixed and dissolved in 550 grams of deionized water and stirred for 60 minutes to form a clear solution. The solution is then placed in an oven at 60°C for gelation and dried for 24 hours to obtain a hydrogel. The resulting hydrogel is heated to 220°C in a muffle furnace at a heating rate of 0.5°C / min and kept at this temperature for 2 hours, and then the furnace is cooled to obtain the pretreated product PG-220. Next, the PG-220 sample is heated to 900°C at a heating rate of 4°C / min and kept warm for 1 hour to obtain the corresponding product PG-900. The PG-900 sample obtained by pretreatment is crushed and ball milled at a ball-to-material ratio of 3:1, and the ball milling speed is 200r / min.
[0071] The second step is the sintering step. The ball-milled sample powder is placed in a C / C composite material mold with a diameter of 20 mm and sintered using spark plasma sintering technology. The sintering parameters are a heating rate of 150°C / min, a sintering temperature of 2400°C, a sintering pressure of 60MPa, and a holding time of 10min; then the furnace is cooled. Through this sintering process, a dense, high-strength bulk carbon material is finally obtained. Figure 1 and Figure 2 This is the carbon material prepared in Example 1.
[0072] Example 2
[0073] A method for preparing a three-dimensional network graphene / amorphous carbon composite material, which differs from Example 1 in that the water-soluble sugar glucose is replaced with sucrose, and the PG-220 sample is heated to 500°C at a heating rate of 4°C / min; other preparation conditions are the same as Example 1.
[0074] Example 3
[0075] A method for preparing a three-dimensional network graphene / amorphous carbon composite material, which differs from Example 1 in that the sintering method is replaced by hot pressing sintering instead of spark plasma sintering, and the specific condition parameters are: heating rate of 10°C / min, sintering temperature of 2300°C, sintering pressure of 40MPa, and holding time of 120min. Other preparation conditions are the same as Example 1.
[0076] Comparative Example 1
[0077] This comparative example adopts the preparation process of CN 115849362A to prepare the carbon material, and the specific steps are:
[0078] Step 1: Preparation of mixed solution, initiation of gelation and preliminary dehydration:
[0079] Weigh 1.2 g of analytically pure N,N'-methylenebisacrylamide and put it into a beaker, add 90 g of deionized water, stir thoroughly to dissolve and clarify, slowly add 180 g of analytically pure glucose monohydrate while stirring in a 60°C water bath, dissolve until clarified, naturally cool to 40°C, slowly add 36 g of analytically pure acrylamide, and continue stirring until the solution is clarified to obtain a mixed solution; drop 0.6 g of a 10 wt% ascorbic acid aqueous solution and a 5 wt% hydrogen peroxide aqueous solution into the mixed solution, quickly stir evenly, pour into a mold, stand and wait for gelation, take out after the gel exotherm ends, obtain a hydrogel block, cut into pieces, put into an oven at 100°C for drying and dehydration for 48 hours, and obtain a xerogel;
[0080] Step 2: Gel heat treatment and powder preparation:
[0081] A large amount of dry gel with free water removed is placed in the inner lining of the reactor, and analytical pure acetone is poured in to make the liquid level reach 2 / 3 of the volume. The lid is tightly covered and sealed in the outer lining. The sealed reactor is placed in an oven and the program is set to keep warm at 200°C for 8 hours. After the insulation is completed, it is cooled to room temperature. The block material in the reactor is taken out and the surface liquid is dried; the taken out block material is mechanically crushed to screen out particles below 20 mesh, and the particles are divided into two portions and poured into two planetary ball mills with a volume of 1L respectively, with a material-ball ratio of 1:1, of which the matching Zirconia ball milling beads occupy 1 / 3 of the volume, and the ball milling media are zirconia beads with particle sizes of 5mm, 10mm and 15mm. The mass ratio of 5mm, 10mm and 15mm zirconia beads is 5:3:2; the parameters of the planetary ball mill are set as follows: first run at a speed of 500r / min for 10min, then adjust to 360r / min and continue to run for 6h before shutting down, and the ground powder is passed through a 100-mesh sieve and sealed to prevent moisture. Finally, about 76g of powder raw material can be screened out from each jar.
[0082] Step 3: Warm pressing, carbonization and graphitization:
[0083] 32 g of the prepared raw material powder was weighed and loaded into a Φ50 mm graphite mold for warm pressing. The temperature was slowly increased at a rate of 3°C / min and uniaxial pressurization was performed. The temperature was kept at 180°C, 220°C, 260°C and the highest temperature of 300°C for 30 minutes respectively, then the temperature was reduced to 220°C at a rate of 2°C / min and naturally cooled to room temperature to obtain a prefabricated body. The pressure reached a peak of 8 tons before keeping at 260°C, and slowly dropped to 6 tons before keeping at 300°C. No additional loading was performed during the cooling stage, and the temperature was unloaded when it dropped to below 200°C. After cooling to room temperature, the pressed body was taken out, and the mass of the body was about 27 g.
[0084] The pressed body is placed in a tubular furnace with an argon atmosphere at 1000°C for 1 hour to obtain a carbonized block, with a heating rate of 3°C / min and a cooling rate of 2°C / min. After cooling to 400°C, it can be cooled naturally. The carbonized block is then graphitized at 3000°C for 10 hours and finally cooled to room temperature to obtain a graphitized block, from a pressed block to a graphitized block.
[0085] The compressive strength of the carbon material prepared according to the above steps is 112MPa; the flexural strength is 57MPa. By comparing the mechanical effect data of the three samples in Example 1, it can be clearly seen that the mechanical strength of the carbon material prepared in Comparative Example 1 is much lower than that of the three-dimensional network graphene / amorphous carbon composite material prepared in Example 1.
[0086] Figure 1 This is a bending strength curve of the three-dimensional network graphene / amorphous carbon composite material of Example 1;
[0087] Figure 2 This is a compression strength curve of the three-dimensional network graphene / amorphous carbon composite material prepared in Example 1;
[0088] Figure 3 This is a microstructure diagram of the three-dimensional network graphene / amorphous carbon composite material prepared in Example 1;
[0089] Figure 4 The wear rate diagram of the three-dimensional network graphene / amorphous carbon composite material prepared in Example 1, the wear test conditions are: during the friction and wear test, the pure carbon block sample is in contact with the alumina ball through linear reciprocating motion at room temperature, the load is set to 5N, the friction speed is 0.1m / s, the stroke is 2.5mm, and the friction lasts for 60 minutes. Figure 4 It can be seen that the volume wear rate of the three-dimensional network graphene / amorphous carbon composite material prepared in Example 1 is 2.63×10 -8 mm 3 / (Nm), proving that the three-dimensional network graphene / amorphous carbon composite material prepared by the present invention has high wear resistance.
[0090] In summary, the above results show that the two-step strategy adopted by the present invention successfully prepares a graphite / amorphous carbon composite material with excellent mechanical properties. By using polyacrylamide and water-soluble sugar hydrogel as starting materials, the prepared composite material has a compressive strength of up to 303MPa and a flexural strength of 203MPa (Example 1), which is significantly better than the carbon material prepared by the traditional graphite-based carbon material and the comparative example 1. That is, the present invention effectively solves the problems of complex preparation process, long cycle, high raw material cost, poor mechanical properties, etc. of traditional graphite block carbon materials. At the same time, the present invention reduces production costs, shortens the preparation cycle, and breaks through the bottleneck of the prior art in material microstructure design by simplifying the process. The high strength and high performance of the composite material have laid the foundation for the widespread application of graphite-based materials in the industrial field, especially in high-tech fields such as aerospace, electronics, and metallurgy. It has huge application potential. Therefore, the present invention not only has significant technical advantages, but also has higher economic and social benefits.
[0091] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing an ultra-high-strength three-dimensional mesh graphene / amorphous carbon composite material, characterized in that: The following steps are involved: A two-step method is adopted to sequentially pretreat and sinter a hydrogel prepared from acrylamide, water-soluble sugars, and N,N'-methylenebisacrylamide, and finally prepare the ultra-high-strength three-dimensional network graphene / amorphous carbon composite material; Wherein, the sintering process adopts spark plasma sintering or hot pressing sintering.
2. The method for preparing an ultra-high-strength three-dimensional network graphene / amorphous carbon composite material according to claim 1, characterized in that: The preparation process of the hydrogel is as follows: The acrylamide, water-soluble sugar and N,N'-methylenebisacrylamide are mixed and dissolved in deionized water, and stirred evenly; and then dried at 50-200° C. to obtain a hydrogel.
3. The method for preparing an ultra-high-strength three-dimensional network graphene / amorphous carbon composite material according to claim 1, characterized in that: According to weight percentage, the usage of acrylamide, water-soluble sugar and N,N'-methylenebisacrylamide are 1-30%, 5-60% and 0.05-3% respectively, and the balance is deionized water.
4. The method for preparing an ultra-high-strength three-dimensional network graphene / amorphous carbon composite material according to claim 3, characterized in that: In terms of weight percentage, the amounts of acrylamide, water-soluble sugar and N,N'-methylenebisacrylamide are 7.39%, 24.65% and 0.18% respectively.
5. The method for preparing an ultra-high-strength three-dimensional network graphene / amorphous carbon composite material according to claim 1, characterized in that: The pre-processing process is: The hydrogel is subjected to heat treatment to obtain a pre-treated product A; The pre-treated product A is heated to 400°C-1400°C at a heating rate of 1-20°C / min under an inert environment, and then kept at this temperature for 1 hour to obtain a pre-treated product B; The pretreated product B is crushed and ball-milled to obtain pretreated powder.
6. The method for preparing an ultra-high-strength three-dimensional network graphene / amorphous carbon composite material according to claim 5, characterized in that: The conditions of the heat treatment process are: The temperature is raised to 140-350°C at a heating rate of 0.1-20°C / min, and maintained for 0.5-30h after reaching the target temperature.
7. The method for preparing an ultra-high-strength three-dimensional network graphene / amorphous carbon composite material according to claim 5, characterized in that: The inert environment is vacuum or argon or nitrogen.
8. The method for preparing an ultra-high-strength three-dimensional network graphene / amorphous carbon composite material according to claim 5, characterized in that: The ball milling treatment conditions are: ball-to-material ratio 1-20:1, ball milling speed 100-600r / min, and ball milling time 6-48h.
9. The method for preparing an ultra-high-strength three-dimensional network graphene / amorphous carbon composite material according to claim 1, characterized in that: The parameters of the sintering process are: heating rate 5-300°C / min, sintering temperature 1600-2800°C, applied pressure 10-200MPa, and holding time 1-120min.
10. An ultra-high strength three-dimensional mesh graphene / amorphous carbon composite material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of block carbon / graphite material based on saccharide small molecules
CN115849362A
Method for fixing carbon in saccharides and preparing high-purity carbon (graphite) material
CN104176725A
Preparation method of compact block ceramic material
CN107954715A
High-strength foamy carbon and preparation method thereof
CN109665861A
Self-assembled boron carbide-graphene composite ceramic and preparation method thereof
CN109928757A